PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA PRODUK KOSMETIK MAKE OVER PADA MAHASISWI PENDIDIKAN EKONOMI UNIVERSITAS RIAU - Nadhila, Nadhila; Kartikowati, Rr. Sri; RM. Riadi, RM. Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aimed to an indicator of the influence of the product quality variable (X1) on purchasing decisions (Y) and the effect of the price variable (X2) on purchasing decisions (Y). This research uses descriptive quantitative method. The population in this stud students of Economic Education of class 2016, 2017, 2018 and 2019 had used MAKE OVER products and who still used MAKE OVER products. While the number of samples in this study were 72 respondents. Data collection techniques in this study were compiled through a questionnaire instrumen that was distributed using a goggle form. Technique data analysis technique used was the coefficient of determination (R2) and the multiple linear regression test. The results in this study indicate that the quality of the product has an effect on purchasing decisions where the tcount is 3.102 ≥ ttable 1.994 and a significant value is 0.003 ≤ 0.05. Price has a significant effect on purchasing decisions where it is obtained t count 9,377 ≥ t table 1,994 and a significant value of 0,000 ≤ 0.05. Multiple linear equation regression Y =. The results of the research coefficient of determination (R2) obtained a value of 0.780 or 78.0%, meaning that this indicates that the variable product quality (X1), price (X2) together have an effect on purchasing decisions 78.0%, and the rest (22.0%). %) found by other factors not included in the study.Key Words : Purchase Decision, Product Quality, Price